全球化学品统一分类和 标签制度(全球统一制度) - 第五修订版 - Nations Unies (United Nations, 2016)
The Globally Harmonized System of Classification and Labelling of Chemicals (GHS) addresses classification and labelling of chemicals by types of hazards. It provides the basis for worldwide harmonization of rules and regulations on chemicals and aims at enhancing the protection of human health and the environment during their handling, transport and use by ensuring that the information about their physical, health and environmental hazards is available. The fifth revised edition includes, inter alia, a new test method for oxidizing solids, new miscellaneous changes to further clarify the criteria for the hazard classes skin corrosion/irritation, severe eye damage/irritation and aerosols; revised and simplified classification and labelling summary tables; new codes for pictograms and revised and further rationalized precautionary statements.